Productive Economy Through Marketing Innovation Development - Bayu Wijayantini (Jurnal Aplikasi IPTEK Indonesia, 2019)
Another specific goal is to help create prosperity and comfort in community life. Through this service activity the target team is partners producing products that are safe, hygienic, healthy and halal. The expected target in this activity is the target partners to have new knowledge and skills and utilization of science and technology, including creative marketing through social media (one of which is open stalls), packaging improvements and product diversification to provide product added value, able to compile simple financial reports and managerial business, in order to optimize production, so that there is an increase in income and welfare for partners and the surrounding environment. Through this Community Partnership Program, it is expected that the knowledge, motivation and enthusiasm of partners will increase. This activity is at least able to increase the spirit of entrepreneurship in household business members BAROKAH and RAHMAH.